Study of Entrepreneurship and Evaluation of Development of Contemporary Entrepreneur in 21st Century - Hossain, K A (Transactions on Engineering and Computing Sciences, 2025)
Harvard Business School characterizes entrepreneurship as “the pursuit of opportunity beyond the resources currently controlled.” The potential of entrepreneurship to drive economic growth and development is significant, applicable to both individual nations and the global landscape, provided that favorable conditions are in place and individuals pursue entrepreneurship with the appropriate motivations. Entrepreneurship encompasses a diverse array of fields, including economics and incentives, markets, management and opportunity, processes, sociology and influence, norms, psychology and motivation, anthropology and history, values and culture, regionalism, regulation and firm structure, research and development, as well as technology and engineering, among others. Innovation and modernization frequently correlate with successful entrepreneurship. The business landscape operates within a dynamic framework, driven by emerging technologies, evolving consumer preferences, and various influencing factors. In response to these changes, individuals in the business sector must remain attuned to market dynamics to recognize opportunities for innovation and address potential risks and concerns. To establish an environment that promotes creative thinking and the generation of new ideas, individuals in leadership positions, including founders, CEOs, managers, and team members across all levels, can gain the essential knowledge, qualities, and skills needed to nurture innovation within the workplace and achieve sustainable success for their organization. This is an analytical article to evaluate and discuss the concept of modern entrepreneurship and development of contemporary entrepreneurs in 21st century.